PENGARUH BEBERAPA METODE STERILISASI TANAH TERHADAP STATUS HARA, POPULASI MIKROBIOTA, POTENSI INFEKSI MIKORISA DAN PERTUMBUHAN TANAMAN - Vita Ratri Cahyani (Sains Tanah - Jurnal Ilmu Tanah dan Agroklimatologi, 2009)
Title : The Effect of Soil Sterilization Methods on Nutrient Status, Population of Microbiota, Potential Infectivity of Mycorrhiza and Plant Growth. The present study was aimed at elucidating the effectivity of soil sterilization methods and the effect on nutrient status, population of microbiota, potential infectivity of Vesicular-Arbuscular Mycorrhiza (VAM) and plant growth. The experimental design was Completely Randomized Design with single factor treatment. Inceptisol with VAM propagules was used for the experiment. The treatment of soil sterilization methods consisted of 8 levels with 4 replications: P1 (control, no sterilization), P2 (oven sterilization), P3 (autoclave sterilization), P4 (steam sterilization), P5 (methyl bromide sterilization), P6 (formaldehyde sterilization with cover), P7 (formaldehyde sterilization no cover), and P8 (burning sterilization). Data analyzed using Analysis of Variance and followed with Duncan’s Multiple Range Test (DMRT) with 5% of significance level. The results showed that the effectivity of total sterilization (to kill bacteria, fungi and actinomycetes) was demonstrated by burning, autoclave and steam sterilizations. The effectivity of selective sterilization (to only kill fungi) was demonstrated by formaldehyde sterilization with cover. Soil sterilization methods affected soil nutrient status with a variety of nutrients and intensities. Soil sterilization treatments affected the plant growth of soybeans. The plant growth was better in control. The exception was observed for autoclave sterilization which increased plant growth. The potential infectivity of VAM and nodulation were suppressed totally by burning, autoclave and steam sterilizations, followed by formaldehyde sterilizations with and without cover. Keywords: effectivity, nutrient status, plant growth, potential infectivity of Mycorrhiza, soil sterilization method